Pengaruh Model Conceptual Understanding Procedures Berbantuan PhET Simulation terhadap Hasil Belajar IPA SMP - Nur Hidayah; Yuberti; Ardian Asyhari (WISE Pendidikan Indonesia, 2026)
This study examined the effect of the Conceptual Understanding Procedures (CUPs) learning model assisted by PhET Simulation on junior secondary students' science learning outcomes. The study was motivated by low cognitive achievement in Grade VIII science, particularly motion concepts, and by the need for instruction that combines structured conceptual negotiation with interactive visualization. A quasi-experimental nonequivalent control group design was employed with 60 Grade VIII students at MTs Muhammadiyah Sukarame Bandar Lampung. Class VIII A served as the experimental class and learned through CUPs assisted by PhET Simulation, whereas Class VIII B received direct instruction. Data were collected using pretest and posttest instruments, classroom-observation sheets, and documentation. The test instrument met the criteria of validity, reliability, difficulty level, and discrimination index. The experimental class obtained a higher posttest mean score (82.13) than the control class (70.27). The independent-samples t-test indicated a significant difference, t(58)=5.78, p<0.001, with a large effect size (Cohen's d=1.49). The N-gain score of the experimental class was 0.71, while the control class reached 0.49. These findings indicate that CUPs assisted by PhET Simulation strengthens conceptual understanding, cognitive engagement, and science learning outcomes by integrating individual reasoning, triplet discussion, whole-class negotiation, and interactive visualization. The study implies that science teachers should combine guided simulation worksheets with structured conceptual dialogue to support meaningful reconstruction of motion concepts.